PERSONAL INCOME TAX AND OUTPUT VOLATILITY: EMPIRICAL EVIDANCE FROM BULGARIA - Tanchev , Stoyan (Revista Inclusiones, 2021)
This article studies the influence of personal income tax in Bulgaria under business cycle. With quarterly data of Eurostat and National Statistical Institute of Bulgaria for the period 1995-2020, the Hodrick-Prescott filter, correlations and regression model between the output gap and the changes in the trend shares and the cyclical shares of personal income tax revenue in GDP, in this paper is compare the cyclical impact of the progressive and the proportional income taxes. Proportional income tax replaced progressive income tax in 2008. The research examined two periods of personal income tax revenue. The first period covered March 1995 through December 2007 with 36 observations. The second period covered March 2008 through March 2020 with 49 observations. The first period examined the progressive income tax. The second period examined the proportional income tax. The research results show that automatic changes in proportional income tax revenue are countercyclical in period of deflation and procyclical in period of inflation. The discretionary changes in proportional income tax revenue are procyclical in period of inflation and deflation. Automatic changes in progressive income tax revenue are countercyclical in period of inflation and deflation. The discretionary changes in progressive income tax revenue are countercyclical in period of deflation and procyclical in period of inflation. It may be inferred that discretion and au